2023
DOI: 10.3389/fimmu.2023.1285088
|View full text |Cite
|
Sign up to set email alerts
|

In-depth blood immune profiling of Good syndrome patients

Alba Torres-Valle,
Larraitz Aragon,
Susana L. Silva
et al.

Abstract: IntroductionGood syndrome (GS) is a rare adult-onset immunodeficiency first described in 1954. It is characterized by the coexistence of a thymoma and hypogammaglobulinemia, associated with an increased susceptibility to infections and autoimmunity. The classification and management of GS has been long hampered by the lack of data about the underlying immune alterations, a controversy existing on whether it is a unique diagnostic entity vs. a subtype of Common Variable Immune Deficiency (CVID).MethodsHere, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Similar to our study, Torres-Valles et al. also reported reduced B-cell counts in the patients diagnosed as Good’s syndrome (GS), a rare immunodeficiency by coexistence of a thymoma and hypogammaglobulinemia, and MG have also been frequently reported in GS patients ( 42 ). Rituximab treatment eliminates most CD20-positive B cells, including memory cells.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our study, Torres-Valles et al. also reported reduced B-cell counts in the patients diagnosed as Good’s syndrome (GS), a rare immunodeficiency by coexistence of a thymoma and hypogammaglobulinemia, and MG have also been frequently reported in GS patients ( 42 ). Rituximab treatment eliminates most CD20-positive B cells, including memory cells.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that autoreactive cytotoxic T cells derived from aberrant T cell maturation in the thymic tumor microenvironment may be involved in B cell lymphopenia ( 41 ), but the pathogenesis of GS is largely unknown. A recent study by Torres-Valle and colleagues demonstrated that immune defects in GS patients involve not only B and T cells, but also several populations of innate immune cells ( 42 ), suggesting that GS may represent an interesting model to investigate the immune dysregulation mechanisms underlying the association between autoimmunity and thymic epithelial tumors.…”
Section: Autoimmune Diseases and Thymic Epithelial Tumorsmentioning
confidence: 99%